Video game simulation on car driving: Analysis of participants' gaze behavior and perception of usability, risk, and visual attention - de Angelo, Juliana Cristina [UNESP]; de Souza Ribeiro, Alexandre [UNESP]; Gotardi, Giseli Chiozi [UNESP]; Medola, Fausto Orsi [UNESP]; Rodrigues, Sérgio Tosi [UNESP] (UNISINOS - Universidade do Vale do Rio Dos Sinos, 2019)
The present article discusses video game simulation applied to research on driving a car. It presents an investigation into the eye movements and perceptual aspects of the research subjects on their interactions in the experimental condition. Investigations into how interactions occur in this interface are important for the development of research. From the perspective of cognitive ergonomics, the objective was to investigate the opinion of the participants on usability, risk, and visual attention and to register the eye movements necessary to control the vehicle in order to complement analyzes of the reported opinions. Applying simultaneous methods of analysis, especially able to explore brain activity such as through visual attention, is important to understand interactions in the human-machine interface. The results demonstrate that eye movements (duration and number of fixations in areas of interest) are similar to non-simulated traffic situations. The usability of the simulator control interfaces are considered to be little similar to non-simulated conditions and modify the mode of driving the vehicle. Despite the reduced immersion provided by the simulator, the perception of risk is present, although very subjective. The reported perception of where visual attention is maintained during vehicle driving is consistent with eye movement tracking records.
Keywords: Simulator video game; Usability; Usability Visual attention; Visual attention